Acquiring And Sharing Knowledge In SMEs: A Case In The Manufacturing Industry - Haapalainen, Päivi; Mäkiranta, Anne (Journal of Knowledge Management Practice, 2013)
Successful knowledge acquiring and sharing plays an important role in the everyday work of any company; these processes are crucial even for companies in manufacturing networks. The aim of this research is to study knowledge acquiring and sharing practices in small and medium sized companies in the manufacturing industry - and especially the information technology (IT) related to these practices. This case study was conducted by interviewing six companies in Western Finland. The findings show that various tools are used in companies for acquiring and sharing knowledge across the organizational borders. However, the assisting role of IT in the process is vague: IT is used and companies believe that it can help the process, but there are various problems and doubts related to it.
Keywords: Knowledge management processes; Acquiring knowledge; Knowledge sharing; Manufacturing networks